Exploring the association of Fermi sources with Young Stellar Objects - Munar-Adrover, P. (2010)
Massive protostars have associated bipolar outflows which can produce strong shocks when interact with the surrounding medium. Some theoretical models predict that particle acceleration at relativistic velocities can occur leading to gamma ray emission. In order to identify young stellar objects (YSO) that might emit gamma rays, we have crossed the Fermi First Year Catalog with catalogs of known YSOs, obtaining a set of candidates by spatial correlation. We have conducted Montecarlo simulations to find the probability of chance coincidence. Our results indicate that ∼70% of the candidates should be gamma-ray sources with a confidence of ∼5ρ. σ International Astronomical Union 2011.